2016
DOI: 10.1182/blood.v128.22.3633.3633
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Quality of Life in Thalassemia Patients; Results from the Intercontinenthal Collaborative Study

Abstract: Thalassemia is one of the most common causes of inherited anemia worldwide. While significant advances has been made in clinical management of thalassemia patients over the past few decades, our knowledge on the factors affecting the quality of life of thalassemia patients is limited. The "IntercontinThal Study" is a collaborative effort to study the quality of life (QoL) and quality of care of thalassemia patients in populations across diverse social and health care systems. Data presented here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
6
11
0
Order By: Relevance
“…The Psychosocial Health Summary Score was consistently found to be lower compared to the Physical Health Summary Score in previous studies conducted in Malaysia [7][8][9], Thailand [10][11][12] or the Middle East [16,31,32]. We found that the school functioning dimension had the lowest mean score in this study.…”
Section: Discussionsupporting
confidence: 51%
“…The Psychosocial Health Summary Score was consistently found to be lower compared to the Physical Health Summary Score in previous studies conducted in Malaysia [7][8][9], Thailand [10][11][12] or the Middle East [16,31,32]. We found that the school functioning dimension had the lowest mean score in this study.…”
Section: Discussionsupporting
confidence: 51%
“…The Psychosocial Health Summary Score was consistently found to be lower compared to the Physical Health Summary Score in previous studies conducted in Malaysia(7-9), Thailand (10)(11)(12) or the Middle East (16,31,32). We found that the school functioning dimension had the lowest mean score in this study.…”
Section: Discussionsupporting
confidence: 51%
“…This is in agreement with a previous study by Amid et al, who investigated QOL in 59 -TM and 39 -TI patients and found that higher hemoglobin levels were significantly associated with better QOL. 26 Lower hemoglobin levels indicate more ineffective erythropoiesis and peripheral hemolysis, which lead to a cascade of subsequent pathophysiological events and clinical complications throughout the course of the disease. 27 In contrast, O'Donnell et al found that children with transfusion-independent anemia have a remarkable facility to adapt to low hemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%